A Zn II -Based Metal–Organic Framework with a Rare tcj Topology as a Turn-On Fluorescent Sensor for Acetylacetone - Yao, Shu-Li; Liu, Sui-Jun; Tian, Xue-Mei; Zheng, Teng-Fei; Cao, Chen; Niu, Chun-Yuan; Chen, Yong-Qiang; Chen, Jing-Lin; Huang, Haiping; Wen, He-Rui (Inorganic chemistry, 2019)
A Zn -based metal-organic framework (MOF) with a rare tcj topology has been solvothermally synthesized and displays relatively good thermal and chemical stabilities. Interestingly, the MOF can sensitively and selectively sense acetylacetone (acac) via a fluorescence enhancement effect with a detection limit of 0.10 ppm and good reusability, which demonstrates the first example of a MOF-based turn-on fluorescent sensor for acac.